Risk factors of postoperative cerebral hyperperfusion syndrome and its relationship with clinical prognosis in adult patients with moyamoya disease - Zhiyong Shi; Lingyun Wu; Yi Wang; Huasheng Zhang; Yongbo Yang; Chunhua Hang (Chinese Neurosurgical Journal, 2023)
Abstract Background To investigate the incidence, risk factors, and clinical prognosis of cerebral hyperperfusion syndrome (CHS) after superficial temporal artery-middle cerebral artery anastomosis combined with encephalo-duro-arterio-synangiosis (STA-MCA/EDAS) in adult patients with moyamoya disease (MMD). Methods The clinical data of 160 adult patients with MMD treated by STA-MCA/EDAS from January 2016 to January 2017 were retrospectively analyzed. According to CHS diagnosis, MMD patients were divided into CHS and non-CHS group. Univariate and multivariate analysis of risk factors and Kaplan-Meier curve of stroke-free survival for CHS were performed. Results A total of 12 patients (7.5%) developed postoperative CHS, of which 4 patients (2.5%) presented with cerebral hemorrhage. Univariate and multivariate analysis showed moyamoya vessel on the surgical hemisphere (OR = 3.04, 95% CI = 1.02–9.03, P = 0.046) and left operated hemisphere (OR = 5.16, 95% CI = 1.09–21.34, P = 0.041) were independent risk factors for CHS. The other variables, such as age, gender, presentation, hypertension, diabetes, smoking, mean mRS score on admission, modified Suzuki stage and pre-infarction stage on surgical hemisphere, and bypass patency, had no association with postoperative CHS (P > 0.05). At final follow-up with average 38 months, there were 18 out of 133 patients (13.5%, 4.91% per person year) presented with newly developed complications. There was no significant difference between newly developed complications, mean mRS scores, and Kaplan-Meier curve of stroke-free survival in patients with and without CHS (P > 0.05). Conclusion The concentration of moyamoya vessels and left operated hemisphere was independent risk factors for CHS, which could not affect the clinical prognosis if treated timely and properly. The current study offers a new perspective of moyamoya vessels and supporting data for choosing MMD candidates on cerebral revascularization.